2007
DOI: 10.1504/ijvsmt.2007.011426
|View full text |Cite
|
Sign up to set email alerts
|

Developing a virtual prototype of a rack and pinion steering system

Abstract: The operation of an automobile steering gear is intermittent with low angular velocities and frequent direction reversals. For a typical Rack and Pinion Steering (RPS) gear used in light vehicles, the span of movement of the rack is limited to approximately four rotations of the pinion. For this limited span of rack travel, the torque required to rotate the pinion is tested for satisfactory functioning of the steering gear. The torque variation due to engagement and disengagement of the pinion teeth, mesh fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In order to prevent these undesirable phenomena, a yoke spring is introduced in the rack and pinion gear. A plunger is placed on the yoke spring and against the rack gear while a yokenut is placed under the yoke spring [17]. The compressive force of the yoke spring is controlled by tightening the yokenut, and by this compressive force, the backlash of the rack and pinion gear can be prevented.…”
Section: Rack and Pinion Gear Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prevent these undesirable phenomena, a yoke spring is introduced in the rack and pinion gear. A plunger is placed on the yoke spring and against the rack gear while a yokenut is placed under the yoke spring [17]. The compressive force of the yoke spring is controlled by tightening the yokenut, and by this compressive force, the backlash of the rack and pinion gear can be prevented.…”
Section: Rack and Pinion Gear Modelmentioning
confidence: 99%
“…When a vehicle goes on the road with a bank angle, the force acting on the tires is shown Figure 7. However, as mentioned in Chapter 2 and 3, there are several forces that hinder the tires from turning and therefore, Equation ( 1) is modified and the tire turning force can be represented as Equation (17).…”
Section: Integration Of Acting Forces On Tiresmentioning
confidence: 99%
“…The magnitude of force variation thus obtained is validated with the design calculations and the result of this research says; the dynamic force magnitudes obtained and found in Adams are closely matching. Kamble and Saha (2007) [4], developed virtual prototype model of rack and pinion gear steering system with incorporated manufacturing error. They used ADAMS software for simulation.…”
Section: Literature Surveymentioning
confidence: 99%
“…Hence, a yoke nut is fixed to the vehicle frame while the plunger rests against the rack with a yoke spring between the yoke nut and plunger. 23 The position of the yoke nut determines the yoke clearance and the compressive force of the yoke spring; therefore it has an influence on the backlash. However, friction is also generated on the contact surface of the rack and the plunger.…”
Section: Rack-and-pinion Gearmentioning
confidence: 99%